Pertumbuhan Empat Varietas Sawi yang Diaplikasikan Pupuk Hayati Mikoriza, Penambahan Bahan Organik dan Nutrisi Tanaman Dengan Sistem Budidaya Organik di Kawasan Taman Udayana - Wahyu Astiko; MT Fauzi; I Muthahanas (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Astiko W, Fauzi MT, Muthahanas I. 2021. Growth of four mustard varieties on applying mycorrhizal biological fertilizer, addition of organic materials and plant nutrients using organic cultivation systems in the Udayana Park area. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 72-79. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Organic mustard greens are one of the most popular agricultural products in the Udayana Park area. This product when sold fresh at harvest has a high price with a fairly high price difference if sold in the conventional market. The purpose of this community service is to determine the growth and yield of four mustard varieties in the application of mycorrhizal biological fertilizers, cow drum fertilizers, and inorganic nutrients in the Udayana Park area. The demonstration plot method was carried out using a completely randomized design using four mustard varieties, namely: V1: Dakota, V2: Kumala, V3: Shinta, and V4: Tosakan with three replications, so that 12 experimental plots were obtained. Parameters observed were plant height at 14 and 28 days after planting (cm), a number of leaves at 14 and 28 dap (cm), wet weight of 35 dap (g/plant), and dry weight of 35 dap (g/plant). The data were analyzed using analysis of variance (ANOVA) and if there was a significant difference, it was continued using the Least Significant Difference test at the level of 5%. The results of the demonstration plot showed that mycorrhizal biofertilizer was given at a dose of 5 t/ha with the addition of cattle manure fertilizer (12 t/ha) accompanied by the provision of plant inorganic nutrients (375 kg/ha urea, 310 kg/ha SP 36 and 225 kg/ha KCl) can increase the height, a number of leaves, wet and dry weight of the Shinta variety. The Shinta variety is the best variety to produce the highest mustard yield.